Blueprint : Cleanmax Technology (EzVac) / Muhammad Zahirrudin Yunos, Muhammad Amin Hamdan and Muhammad Aiman Ab Manaf - Yunos, Muhammad Zahirrudin; Hamdan, Muhammad Amin; Ab Manaf, Muhammad Aiman (2021)
The EzVac cleaner is an invention of the latest vacuum cleaner available on the market. Many special features and technology in this vacuum make it different from others. To produce high-quality tools, the materials used should be of high quality and use the current technology to make cleaning more easier. For future technology, we will try to make this EzVac cleaner moves of its own and improve the sensors such as cliff sensors, bump sensors, wall sensors, and optical encoders. All these sensors are important to move vacuum to navigate their way around the customer’s home.